PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS IV SD NEGERI 012 TAMBUSAI UTARA KABUPATEN ROKAN HULU TAHUN AJARAN 2016 / 2017 - Nurmi Is (STKIP Rokania Pasir Pangaraian, 2018)
This research is a classroom action research that aims to improve the learning outcomes of fourth grade students at SD Negeri 012 Tambusai Utara T.A 2016/2017. The use of picture media is proven to improve the quality of learning. From the observation of the activity the teacher has shown that the use of media images is very good. Can be seen from the scores obtained in the first cycle of 70% with the perfect category increasing to 86.6% in the second cycle with a very perfect category. The use of picture media is proven to increase student activity. From the results of observations indicate that student activity increases. In the first cycle the activity of students reached 66.6% with a high category and in the second cycle obtained a value of 88.3% with a very high category. By using image media proven to be able to improve the ability of students individually to absorb the subject matter that has been given. This is evident from the number of students who complete. In the first cycle as many as 74% of students who completed and in the second cycle as many as 93% of students who completed